Impact of Sapien 3 Balloon-Expandable Versus Evolut R Self-Expandable Transcatheter Aortic Valve Implantation in Patients With Aortic Stenosis: Data From a Nationwide Analysis. Issue 4 (28th January 2020) - Deharo, Pierre; Bisson, Arnaud; Herbert, Julien; Lacour, Thibaud; Saint Etienne, Christophe; Grammatico-Guillon, Leslie; Porto, Alizée; Collart, Frederic; Bourguignon, Thierry; Cuisset, Thomas; Fauchier, Laurent
Abstract : Background: Two competing transcatheter aortic valve replacement (TAVR) technologies are currently available. Head-to-head comparisons of the relative performances of these 2 devices have been published. However, long-term clinical outcome evaluation remains limited by the number of patients analyzed, in particular, for recent-generation devices. Methods: Based on the French administrative hospital-discharge database, the study collected information for all consecutive patients treated with a TAVR device commercialized in France between 2014 and 2018. Propensity score matching was used for the analysis of outcomes during follow-up. The objective of this study was to analyze the outcomes of TAVR according to Sapien 3 balloon-expandable (BE) versus Evolut R self-expanding TAVR technology at a nationwide level in France. Results: A total of 31 113 patients treated with either Sapien 3 BE or Evolut R self-expanding TAVR were found in the database. After matching on baseline characteristics, 20 918 patients were analyzed (10 459 in each group with BE or self-expanding valves). During follow-up (mean [SD], 358 [384]; median [interquartile range], 232 [10–599] days), BE TAVR was associated with a lower yearly incidence of all-cause death (relative risk, 0.88; corrected P =0.005), cardiovascular death (relative risk, 0.82; corrected P =0.002), and rehospitalization for heart failure (relative risk, 0.84; corrected P <0.0001). BE TAVR was also associated with lower rates of pacemaker implantation after the procedure (relative risk, 0.72; corrected P <0.0001). Conclusions: On the basis of the largest cohort available, we observed that Sapien 3 BE valves were associated with lower rates of all-cause death, cardiovascular death, rehospitalization for heart failure, and pacemaker implantation after a TAVR procedure. Abstract : Supplemental Digital Content is available in the text.